Experiences with the Catholic Relief Services' clustering process for agroenterprise development and some suggestions for improvement - Murray-Prior, Roy; Concepcion, S.; Batt, Peter; Israel, F.; Apara, D.; Bacus, R.; Rola-Rubzen, Maria Fay; Montiflor, M.; Lamban, R.; Axalan, J.; Real, R. (Australian Centre for International Agricultural Research, 2013)
An evaluation of the Catholic Relief Services’ (CRS) eight-step clustering approach to agroenterprise development was a key focus of the Australian Centre for International Agricultural Research (ACIAR) – Philippine Council for Agriculture, Aquatic and Natural Resources Research and Development (PCAARRD) horticulture project on ‘Enhancing the profitability of selected vegetable value chains in the southern Philippines’. The CRS approach encourages farmers to form small, collaborative marketing groups (clusters) and to facilitate the sustainable development of these clusters. The research, which used participative action learning and action research processes, identified that an enhanced clustering approach should incorporate processes that overcome issues such as: input financing arrangements to replace loans from informal moneylenders and traders; risks associated with production failures and pest and disease problems; maintaining relationships with buyers; and building group resilience and independence so that donor agencies have an exit strategy. The research findings suggest that to enhance the sustainability of the clusters the CRS eight-step process should be applied to three phases: (i) establishment, (ii) building resilience and (iii) implementing an exit strategy.